Materials Chemistry : For Scientists and Engineers - Benvenuto, Mark Anthony (De Gruyter Textbook, 2022)
This book is an introductory work on the broad topics included in Materials Science. It encompasses a number of different materials classes and properties with a focus on the structure-property relationships between them. Each class of materials will include and discuss recycling techniques and other green methods of production. Materials Chemistry: For Scientists and Engineers is ideal for all newcomers to the fi eld as well as for those seeking a knowledge of solid state chemistry.